Bromodomain-containing-protein-4 and cyclin-dependent-kinase-9 inhibitors interact synergistically in vitro and combined treatment reduces post-traumatic osteoarthritis severity in mice. Issue 1 (January 2021) - Fukui, T.; Yik, J.H.N.; Doyran, B.; Davis, J.; Haudenschild, A.K.; Adamopoulos, I.E.; Han, L.; Haudenschild, D.R.
Summary: Objective: Joint injury rapidly induces expression of primary response genes (PRGs), which activate a cascade of secondary genes that destroy joint tissues and initiate post-traumatic osteoarthritis (PTOA). Bromodomain-containing-protein-4 (Brd4) and cyclin-dependent-kinase-9 (CDK9) cooperatively control the rate-limiting step of PRG transactivation, including pro-inflammatory genes. This study investigated whether Brd4 and CDK9 inhibitors suppress inflammation and prevent PTOA development in vitro and in a mouse PTOA model. Methods: The effects of Brd4 and CDK9 inhibitors (JQ1 and Flavopiridol) on PRG and associated secondary damage were rigorously tested in different settings. Short-term effects of inflammatory stimuli (IL-1β, IL-6, TNF) on human chondrocyte PRG expression were assessed by RT-PCR and microarray after 5-h. We quantified glycosaminoglycan release from IL-1β-treated bovine cartilage explants after 3–6 days, and osteoarthritic changes in mice after ACL-rupture using RT-PCR (2–24hrs), in vivo imaging of MMP activity (24hrs), AFM-nanoindentation (3–7days), and histology (3days-4wks). Results: Flavopiridol and JQ1 inhibitors act synergistically, and a combination of both almost completely prevented the activation of most IL-1β-induced PRGs in vitro by microarray analysis, and prevented IL-1β-induced glycosaminoglycan release from cartilage explants. Mice given the drug combination showed reduced IL-1β and IL-6 expression, less in vivo MMP activity, and lower synovitis (1.5 vs 4.9) and OARSI scores (2.8 vs 6.0) than untreated mice with ACL-rupture. Conclusions: JQ1 and Flavopiridol work synergistically to reduce injury response after joint trauma, suggesting that targeting Brd4 and/or CDK9 could be a viable strategy for PTOA prevention and treatment of early OA.